Characterization of Starch Extracted from Pretreated Whole-Grain Bambara Groundnut - Adamu Hamsatu Sani; Akubor P. I; Abubakar Ummulkhairu (Kwaghe International Journal of Sciences and Technology, 2026)
This study characterized starch extracted from whole-grain and dehulled Bambara groundnut (Vigna subterranea L.) pretreated with Saccharomyces cerevisiae to determine the effects of dehulling and fermentation on starch yield, composition, functionality, pasting behavior, digestibility, and morphology. Whole-grain Bambara groundnut seeds were soaked for 24 h, manually dehulled where applicable, oven-dried at 40°C to constant weight, and fermented prior to starch extraction. The extracted starches were analyzed using standard methods, and statistical significance was determined at p < 0.05. The results showed that dehulling followed by fermentation significantly increased starch yield from 34.88% to 39.66%. Proximate analysis indicated moisture content of 5.48–6.01%, crude protein of 0.23–0.77%, ash of 0.50–0.61%, crude fat of 0.52–0.96%, fiber of 0.02–0.90%, and carbohydrate content of 90.92–93.20%, suggesting improved starch purity after pretreatment. Functional properties were also enhanced, with water absorption capacity ranging from 2.43 to 1.50 g/100 g, oil absorption capacity from 2.00 to 1.75 g/100 g, loose density from 0.45 to 0.68 g/ml, bulk density from 0.75 to 0.95 g/ml, swelling capacity from 88.68% to 67.45%, dispersibility from 79.00% to 59.00%, and wettability from 30.00 to 7.50 s. Pasting properties improved, with peak viscosity of 174.37–215.65 cP, final viscosity of 223.37–226.42 cP, setback of 67.60–74.48 cP, trough of 155.73–188.29 cP, pasting temperature of 68.30–72.12°C, and pasting time of 3.17–7.17 min. Amylose content increased to 20.50–26.16%, whereas amylopectin decreased to 73.84–79.50% following fermentation. In addition, total starch (61.46–66.75%) and rapidly digestible starch (50.05–63.28%) increased, while resistant starch (13.91–21.80%) and slowly digestible starch (23.54–28.44%) decreased after pretreatment. Scanning electron microscopy further revealed oval, spherical, ring-like, elliptical, and irregular granules with slight surface modification. Overall, the study demonstrates that dehulling and fermentation improve the yield, purity, functional performance, pasting characteristics, and digestibility profile of Bambara groundnut starch, highlighting its potential for food and industrial applications.